Growth assessment of croakers (Pseudotolithus species) in West African waters - Mahe, Kelig; Ekperusi, Abraham O.; Diouf, Khady; Munschy, Catherine; Aminot, Yann; Andrialovanirina, Nicolas; Dussuel, Antoine; Diop, Mamadou (Frontiers in Fish Science, 2024)
IntroductionThe genus Pseudotolithus, commonly called croaker, is represented by the three main species found in West African waters.MethodsIn total, 934 individuals were sampled in 8 locations in Senegal, Ghana, and Nigeria. Several tests identified using sectioned otolith as the best method for determining the croakers' age. The marginal increment analysis validated the age data.ResultsThe relationship between total length and total weight was significant for all species. This relationship is significantly different according to the geographical area. There was significant sexual dimorphism in P. senegalensis and P. typus, and the reproduction period presented a significant effect on the body length-weight relationship of P. senegalensis. The von Bertalanffy growth model constrained by t0 = 0 was the best fit for the observed age data from the three species in the sampled countries. The asymptotic length TL∞ was estimated from 26.6 cm for P. elongatus on the Nigerian coast to 42.2 cm for P. senegalensis on the Senegalese coast. The growth rate K ranged from 0.58 for P. senegalensis to 1.12 for P. typus.DiscussionThe growth was significantly different among the three sampled countries for P. senegalensis. Conversely, there was no significant difference of growth between specimens of P. typus from Nigeria and Ghana. Finally, there was no significant sexual dimorphism in the growth of P. senegalensis in Senegalese waters. This new information on the biology of these three croaker species is essential for the future assessment and management of these commercial species in West African waters.